Handbook of Ancient Afro-Eurasian Economies Volume 2: Local, Regional, and Imperial Economies - Reden, Sitta (De Gruyter, 2021)
In the second volume a wide range of economic actors - from kings and armies to cities and producers - are discussed within different imperial settings as well as the tools which enabled and constrained economic outcomes. A central focus are nodes of consumption that are visible in the archaeological and textual records of royal capitals, cities, religious centers, and armies that were stationed in imperial frontier zones.